Isometric exercises and somatosensory training as intervention programmes for patellofemoral pain in young dancers - Steinberg, N.; Tenenbaum, S.; Waddington, G.; Adams, R.; Zakin, G.; Zeev, A.; Siev-Ne, I. (European Journal of Sport Science, 2020)
Patellofemoral pain (PPF) is a common problem experienced by young dancers. Currently, there is no clear indication as to the optimal intervention programme for reducing the level of pain and improving functional abilities in young dancers with PFP. Our aim was to examine the efficacy of two intervention programmes compared with controls in relation to PFP symptoms (shown by pain level, Grinding test, and patellar inhibition test-PIT) and functional abilities of dancers with PFP. Ninety-eight young dancers (mean age 13.4 ± .97) with PFP were assessed for clinical parameters and functional abilities pre and post an intervention programme lasting 12 weeks. Using cluster sampling controlling for grade and school, the dancers were divided into three groups: isometric exercises (IE), somatosensory training (ST), and control (CO). Post-intervention, significantly lower pain levels upon patellar provocation testing were reported for the two treatment groups compared with controls. There was a significantly lower rate of legs recovered in the CO group compared with both intervention groups on the Grinding test, and on the PIT. Postural balance ability and proprioception abilities were significantly better post-treatment for the two treatment groups compared with controls. A significant interaction showed that hip abduction muscle strength improved more in the IE group. In conclusion, both isometric exercises and somatosensory training were effective for decreasing clinical symptoms and improving some functional abilities in young dancers with PFP. Further studies on these types of interventions could determine the most effective training protocol for prevention and treatment of PFP in young dancers. Keywords: Patellofemoral pain, intervention programme, proprioception ability, postural balance ability, isometric exercises